Review of the applications of microreactors. (July 2015) - Yao, Xingjun; Zhang, Yan; Du, Lingyun; Liu, Junhai; Yao, Jianfeng
Abstract: Microreactors offer excellent mass and heat transfer performance for extraction and multiphase reactions. They provide a powerful tool for process intensification and micro scale processing. This paper reviews the structures of microreactors and units, and their applications on the synthesis of nanoparticles, organics, polymers and biosubstances. The structural evolution and properties of the commercialized and lab-made microreactors are introduced in detail. Recent developments of the fabrication, structures and applications of micro-structured reactors are highlighted. The promising direction in science and technology for future microreaction technology is also discussed.